Regeneration of rodent small intestine tissue following implantation of scaffolds seeded with a novel source of smooth muscle cells. (November 2011) - Basu, Joydeep; Mihalko, Kim L; Payne, Richard; Rivera, Elias; Knight, Toyin; Genheimer, Christopher W; Guthrie, Kelly I; Sangha, Namrata; Jayo, Manuel J; Jain, Deepak; Bertram, Timothy A; Ludlow, John W
Aims: To apply an organ regeneration platform technology of autologous smooth muscle cell/biomaterial combination products, previously demonstrated to be successful for urinary tissue regeneration, to the regeneration of the small intestine.Materials & methods: Patch and tubular constructs were implanted in rodent small intestines and histologically evaluated over a time course for evidence of regeneration of the laminarly organized neo-mucosa and muscle layers.Results: Laminarly organized neo-mucosa and muscle layer bundles are demonstrated as early as 8 weeks postimplantation.Conclusion: An organ regeneration technology platform of autologous smooth muscle cell/biomaterial combination products can be extended to the regeneration of the small intestine.